EP956 Cardiophrenic node dissection during interval debulking surgery for stage IV ovarian cancer: a case series. (1st November 2019) - Pinelli, C; Morotti, M; Casarin, J; Tozzi, R; Ghezzi, F; Alazzam, M; Soleymani Majd, H
Abstract : Introduction/Background: Several studies have demonstrated the feasibility and role of cardiophrenic lymph nodes (CPLNs) resection during primary debulking surgery (PDS) for stage IV ovarian cancer (OC). However, no studies, to date, investigated the role of CPLNs removal during interval debulking surgery (IDS) after neoadjuvant chemotherapy (NACT). Methodology: A retrospective analysis of consecutive stage IV OC patients who underwent NACT followed by IDS with CPLNs resection from July 2017 to June 2018. CPLNs sized >7 mm on the short axis at pre-operative CT-scan were considered for excision if optimal complete resection could be achieved. Results: A total of 21 ovarian cancer stage IV patients treated with NACT followed by IDS were identified. Seven (33.3%) patients underwent CPLNs resection. A partial response to NACT by RECIST criteria was observed in 5 of 7 patients (71%) while 2 cases had stable disease (29%). Complete cytoreduction without residual disease was achieved in 5 cases (71%) while in two cases (29%) optimal cytoreduction was performed. All patients underwent full-thickness right diaphragmatic resection and pleurectomy. All excised CPLNs were found in the right side of the lower anterior mediastinum. Intra-operative surgical complications occurred in one patient. One patient (14%) had a major postoperative complication (Clavien-Dindo 3). Two cases of postoperative cardiac arrhythmia were observed. The final histological examination of the CPLNs revealed metastatic disease in 4 (57%) of 7 patients. Conclusion: CPLNs removal after NACT for stage IV OC is safe and necessary to achieve a complete resection in the context of IDS after NACT. Disclosure: Nothing to disclose.